The Synthesis and Physicochemical Characterization of Hydroxyapatite (HAp) from Local Duck Egg Shells - Agung Rimayanto Gintu; Elizabeth Betty Elok Kristiani; Yohanes Martono (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Hydroxyapatite (HAp) Biocheramics was the main component of remineralisation agent to the hard tissues; it is commonly synthesized from compounds rich with calcium. One of the compounds recommended as a HAp source was eggshells. This study aimed to synthesize the HAp from local duck eggshells containing Calcium 0,8631 ± 0,0015g/g and Phosphor 0,3118 ± 0,0016g/g. The synthesis process of HAp by Base Precipitation methods showed rendement 85,06 ± 1,0135%. The Physicochemical characterization to the HAp showed the Calcium contains 0,4760 ± 0,0027g/g; Phosphor 0,0897 ± 0,0023g/g; Porosity 82,0106 ± 0,4484%; Biodegradability 5,3506 ± 0,0295%; and Swelling ability 5,7678 ± 0,1897%. The results concluded that the local duck egg shells were recommended as HAp sources. Based on characterisation results, the HAp made from it was potentially applied as a remineralization agent.